2016
DOI: 10.14689/ejer.2016.65.02
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Self-Efficacy Perceptions, Learning Oriented Motivation, Lifelong Learning Tendencies of Candidate Teachers: A Modeling Study

Abstract: Teacher self-efficacy perceptions, learning oriented motivation, lifelong learning tendencies of candidate teachers: A modeling study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
1
15
0
4
Order By: Relevance
“…There are also reports on the low level of teacher commitment while they are in service (Mehmood, 2011). A number of studies indicate a positive relationship between teacher motivation and their tendencies towards lifelong learning, their commitment to their job, and their self-efficacy perceptions (Akyol, 2016;Khan, 2017;Mehmood, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports on the low level of teacher commitment while they are in service (Mehmood, 2011). A number of studies indicate a positive relationship between teacher motivation and their tendencies towards lifelong learning, their commitment to their job, and their self-efficacy perceptions (Akyol, 2016;Khan, 2017;Mehmood, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Academic self-efficacy is defined one's self-competency and self-belief in his/her successful accomplishment of academic tasks that are assigned to him/her during education period [32]. The previous studies stated that individuals, who have higher levels of academic self-efficacy, show higher academic performance [47], and there is a positive correlation between self-efficacy perceptions and life-long learning motivations of teacher candidates [60], and between academic self-efficacy and academic motivation [61]. The result of another study conducted on the academic self-efficacy of teacher candidates concluded that those who had better academic achievements (81-90 points) significantly differed from those who had middle (71-80 points) or poor (61-70 points) achievements [42].…”
Section: "Research Question 2 Are the Occupational Anxiety And Academentioning
confidence: 99%
“…The teacher's self-efficacy is not only useful for the teacher himself, it also has impacts on student performance result such as; learning achievement and student efficacy level (Corkett, Hatt, & Benevides, 2016) that explains there is a strong correlation between teacher's efficacy level and student efficacy level, that is also affected on learning achievement level which is getting better. Student efficacy also relates to student motivation (Akyol, 2016), from the research of data analysis shows that motivation level oriented in learning, lifelong learning tendencies and self-efficacy perception toward the high teaching profession of the teacher candidate. So that, the research has strategic function in education, the utilization of the research is not only for the teacher but also for student even school as an institution will also receive its benefit (Friedman & Kass, 2002) class organization is getting better, learning climate is more open, and student academic adjustment, teacher's behavior, and practice pattern, and factors that underlying teacher's psychological welfare, including personal achievement, work satisfaction, and teacher commitment are better (Zee & Koomen, 2016).…”
Section: Introductionmentioning
confidence: 99%